2007
DOI: 10.1088/0964-1726/16/4/055
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of a shape memory alloy based dexterous robot hand

Abstract: Modern externally powered upper-body prostheses are conventionally actuated by electric servomotors. Although these motors achieve reasonable kinematic performance, they are voluminous and heavy. Deterring factors such as these lead to a substantial proportion of upper extremity amputees avoiding the use of their prostheses. Therefore, it is apparent that there exists a need for functional prosthetic devices that are compact and lightweight. The realization of such a device requires an alternative actuation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 34 publications
0
45
0
3
Order By: Relevance
“…Even today, researchers and companies are continuing to develop biomimetic robotic manipulators that are predominantly hard (Bar-Cohen and Breazeal, 2003;Price et al, 2007;Bundhoo et al, 2009;Gilardi et al, 2010;Shin et al, 2010) despite the fact that only just over one-tenth of the human body's weight is skeletal (Kim et al, 2013). The soft nature of the human hand enables it to pick up and interact with a wide variety of objects from a fragile eggshell to a heavy rock.…”
Section: Figure 1 | the Fin Raymentioning
confidence: 99%
“…Even today, researchers and companies are continuing to develop biomimetic robotic manipulators that are predominantly hard (Bar-Cohen and Breazeal, 2003;Price et al, 2007;Bundhoo et al, 2009;Gilardi et al, 2010;Shin et al, 2010) despite the fact that only just over one-tenth of the human body's weight is skeletal (Kim et al, 2013). The soft nature of the human hand enables it to pick up and interact with a wide variety of objects from a fragile eggshell to a heavy rock.…”
Section: Figure 1 | the Fin Raymentioning
confidence: 99%
“…As a continuance of this work, an SMA actuated hand (the Rutgers Hand) was rapid prototyped comprising of 5 fingers and 20 DOF (DeLaurentis and Mavroidis, 2002). Price et al, 2007 showed practical application of shape memory alloys as actuators (Price et al, 2007) in a three-fingered robotic hand (Fig. 4b).…”
Section: Related Researchmentioning
confidence: 99%
“…shape memory alloys [21], air muscles [22], fluidic actuators [6]) have been tried of which electromagnetic motors are still the most successful. Due to volume restrictions, most of the grasping devices use remote actuators with tendon transmissions to drive the finger joints from outside the hand without backlash and other gearing difficulties.…”
Section: Robot Hand Actuationmentioning
confidence: 99%